Sequencing the 500-kb GC-rich symbiotic replicon of Rhizobium sp. NGR234 using dye terminators and a thermostable "sequenase": a beginning. - Freiberg, C; Perret, X; Broughton, W J; Rosenthal, A (Genome Research, 1996)
Genomes of the soil-borne nitrogen-fixing symbionts of legumes [Azo(Brady)Rhizobium species] typically have GC contents of 59-65 mol%. As a consequence, compressions (up to 400 per cosmid) are common using automated dye primer shotgun sequencing methods. To overcome this difficulty, we have exclusively applied dye terminators in combination with a thermostable "sequenase" for shotgun sequencing GC-rich cosmids from pNGR234a, the 500-kbp symbiotic replicon of Rhizobium sp. NGR234. A thermostable sequenase incorporates dye terminators into DNA more efficiently than Taq DNA polymerase, thus reducing the concentrations needed (20- to 250-fold). Unincorporated dye terminators can simply be removed by ethanol precipitation. Here, we present data of pXB296, one of 23 overlapping cosmids representing pNGR234a. We demonstrate that the greatly reduced number of compressions results in a much faster assembly of cosmid sequence data by comparing assembly of the shotgun data from pXB296 and the data from another pNGR234a cosmid (pXB110) sequenced using dye primer methods. Within the 34,010-bp sequence from pXB296, 28 coding regions were predicted. All of them showed significant homologies to known proteins, including oligopeptide permeases, an essential cluster for nitrogen fixation, and the C4-dicarboxylate transporter DctA.